Utilization of Digital Learning for Literacy of Disabled Voters: Case Study of DIGI-EDVOT in the 2024 Election - Muhammad Risal Arifin; Yudha Kurniawan (South Sulawesi Education Development (SSED), 2024)
The implementation of elections is basically a manifestation of people's sovereignty to produce a democratic government. Community participation, including the participation of people with disabilities, is an indicator of election success. However, information accessibility is one of the obstacles faced by voters with disabilities in accessing and receiving election information. Meanwhile, it is an important agenda in inclusive elections to provide and increase political literacy for people with disabilities so that they have adequate knowledge regarding the implementation of elections so that there are no gaps in election knowledge, people with disabilities who do not cast their votes due to a lack of understanding of the voting process, or people with disabilities who only aborting his obligations by giving his vote for free to election participants he doesn't know. Along with the development of digital technology, it has influenced various aspects of life, including aspects of education. The birth of digital learning now makes it easier for people to access all forms of information, learning, and/or knowledge. In this way, through this research, we attempt to present innovative ideas regarding digital learning in the field of politics for people with disabilities, named DIGI-EDVOT (digital learning for disabled young voters). DIGI-EDVOT is a digital learning innovation that focuses on disability political education, which contains complete information about elections such as mechanisms, rights of voters with disabilities, legal protection, and other information. It is hoped that DIGI-EDVOT can be a solution to the problems faced by people with disabilities due to the lack of election information they receive and the inaccessibility of election information. DIGI-EDVOT is also expected to be a golden opportunity to create political socialization, which is digital-based political education, as well as being an innovative contribution to realizing a more inclusive 2024 election.